If b 1 b 2 = 2 ( c 1 + c 2 ) then at least one of the equations x 2 + b 1 x + c 1 = 0 and x 2 + b 2 x + c 2 = 0 has __________ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let D 1 and D 2 denote the discriminants of the first and second quadratic respectively. We have D 1 + D 2 = ( b 1 2 + b 2 2 ) − 4 ( c 1 + c 2 ) = ( b 1 2 + b 2 2 ) − 2 b 1 b 2 = ( b 1 − b 2 ) 2 ≥ 0 . Hence at least one of the the discriminant must be non-negative, i.e., at least one of the equations must have real roots.
If one adds these two quadratic equations together, then the result becomes:
2x^2 + (b1 + b2)*x + (c1 + c2) = 0;
or 2x^2 + (b1 + b2) x + (b1 b2)/2 = 0;
or x^2 + (b1 + b2) x/2 + (b1 b2)/4 = 0 (i).
The roots of (i) are found via the Quadratic Formula:
x = (1/2) * [ -(b1+b2)/2 (+/-) sqrt [((b1+b2)/2)^2 - 4(1)(b1*b2)/4]];
or x = (1/2) * [ -(b1+b2)/2 (+/-) sqrt [((b1^2 + 2 b1 b2 + b2^2) / 4 - (b1*b2)];
or x = (1/2) * [ -(b1+b2)/2 (+/-) sqrt [((b1^2 - 2 b1 b2 + b2^2) / 4];
or x = (1/2) * [ -(b1+b2)/2 (+/-) sqrt [(b1 - b2)^2) / 4];
or x = (1/2) * [ -(b1 + b2)/2 (+/-) (b1 - b2)/2];
or x = -b1/2 or -b2/2.
Both roots for (i) are real for all b1 & b2, hence at least one of the original quadratic equations must have real roots as well.
From Vieta's formulas, we know that if a quadratic equation has real coefficients, but complex roots, the roots must be conjugates. Both the sum and product of conjugates result in a real answer. The roots of the combined equation are potentially each the sum of complex conjugates. So, the conclusion that one of the original equations had to have real roots does not follow, although I believe the conclusion itself is correct.
A more convincing argument can be made by assuming that both original equations have complex conjugate roots. Call them (m + ni), (m - ni), (p + qi) and (p - qi). From Vieta, b1 = -[(m + ni) + (m - ni)] = -2 m. Similarly, b2 = -2 p. Note that both m and p are solutions to the combined equation above, but neither of the original equations has real roots. Continuing, c1 = (m + ni) (m - ni) = m^2 + n^2, and c2 = p^2 + q^2. Then b1 b2 = 4 m p, and 2 (c1 + c2) = 2 (m^2 + n^2 + p^2 + q^2). Equate these results and rearrange terms: m^2 - 2 m p + p^2 + n^2 + q^2 = (m - p)^2 + n^2 + q^2 = 0. This can only be true if all the squared terms are identically zero, contradicting the assumption that all 4 roots were complex conjugate pairs. Consequently, at least one of the original equations has real roots. QED.
(Hello @Tom Engelsman , I tried here to write down your solutions in proper latex)
If one adds these two quadratic equations together, then the result becomes: 2 x 2 + ( b 1 + b 2 ) ∗ x + ( c 1 + c 2 ) = 0 ;
or 2 x 2 + ( b 1 + b 2 ) x + ( b 1 b 2 ) / 2 = 0 ;
or x 2 + ( b 1 + b 2 ) x / 2 + ( b 1 b 2 ) / 4 = 0 ( ∗ ) .
The roots of (*) are found via the Quadratic Formula:
x = ( 1 / 2 ) ∗ [ − ( b 1 + b 2 ) / 2 ± ( ( b 1 + b 2 ) / 2 ) 2 − 4 ( 1 ) ( b 1 ∗ b 2 ) / 4 ] ;
or x = ( 1 / 2 ) ∗ [ − ( b 1 + b 2 ) / 2 ± ( ( b 1 2 + 2 b 1 b 2 + b 2 2 ) / 4 − ( b 1 ∗ b 2 ) ] ;
or x = ( 1 / 2 ) ∗ [ − ( b 1 + b 2 ) / 2 ± ( ( b 1 2 − 2 b 1 b 2 + b 2 2 ) / 4 ] ;
or x = ( 1 / 2 ) ∗ [ − ( b 1 + b 2 ) / 2 ± ( b 1 − b 2 ) 2 ) / 4 ] ;
or x = ( 1 / 2 ) ∗ [ − ( b 1 + b 2 ) / 2 ± ( b 1 − b 2 ) / 2 ] ;
or x = − b 1 / 2 or − b 2 / 2 . Both roots for (*) are real for all b 1 & b 2 , hence at least one of the original quadratic equations must have real roots as well.
Problem Loading...
Note Loading...
Set Loading...
Let us prove it by contradiction. Assume that none of the equations has real solutions. This would imply that both discriminants have to be negative. So b 1 2 < 4 c 1 and b 1 2 < 4 c 2 From these two inequalities we can obtain that c 1 and c 2 have to be positive numbers, and then, using the condition given in the problem, the product b 1 b 2 has to be positive too. Multiplying the inequalities that we mention above, we get that b 1 2 b 1 2 < 1 6 c 1 c 2 . ( ∗ ) Besides that, we know that 4 c 1 c 2 ≤ ( c 1 + c 2 ) 2 , and therefore 1 6 c 1 c 2 ≤ 4 ( c 1 + c 2 ) 2 ( ∗ ∗ ) Combining ( ∗ ) and ( ∗ ∗ ) , we get that b 1 2 b 1 2 < 4 ( c 1 + c 2 ) 2 . ( ∗ ∗ ∗ ) This inequality contradicts the condition b 1 b 2 = 2 ( c 1 + c 2 ) .